The Effect of Regional Investment and Government Spending on Economic Growth - Sendi Gusnandar Arnan; Bachtiar Asikin; R. Wedi Rusmawan Kusumah (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2024)
Economic growth signifies the progressive enhancement of a region's capacity to generate goods and services within a specific timeframe. Achieving high economic growth clearly indicates the successful progress of economic development. This research aims to ascertain the impact of Regional Investment and Expenditures on the Economic Growth of West Java Province. The investigation employed a descriptive methodology. The data was acquired from the Central Statistics Agency Report from 2015 to 2021. The data analysis technique uses the Multiple Linear Regression equation. The research findings indicate that investment and regional expenditure significantly impact economic growth.